COVID-19 and its effect on Olympic sport: The importance of studying social isolation and the harm causes it, in order to minimze it - Ramos e Côrte, A. C.; Camargo-Junior, F.; Chalhub, T.; Morisson de Moraes Filho, J.; Santos, R.; Feitosa, F.; Freire, R.; Benayon, P.; Hausen, M.; Bachini, F.; Wolff, A.; Pereira, G.; et al. (Revista Brasileira de Medicina do Esporte, 2020)
In March 2020, the World Health Organization (WHO) declared the disease caused by the SARS-CoV2 virus, known as COVID-19, to be a pandemic. The sporting world, too, is suffering from the global effects of this disease, with the postponement or cancellation of competitions, including the 2020 Tokyo Olympic Games. As a proposal for containing the disease, social isolation was declared. Despite the importance of this measure, it was harmful for Olympic athletes, as they had to stay away from their training site and trainers, as well as their interdisciplinary teams. It is therefore important to study this harm caused, in order to minimize it. In general, it is believed that regular physical activity is associated with improved immune system functioning. The lack of training can therefore have significant consequences for the performance and health of the Olympic athlete. From the athlete's point of view, the impaired immune system, due to the reduced frequency of physical exercise, leaves them more vulnerable to contracting or developing infections or other diseases. The risk of harm due to the decreased performance of preventive works is also evident in this population. The reductions in training load and intensity can cause changes in the athlete's body composition and affect various aspects of cardiorespiratory fitness, as well as reducing strength levels and muscle potency. In relation to the athlete's mental health, two aspects are particularly challenging: isolation and uncertainty. Based on the possible harm caused by social isolation, the need is seen for a specific and joint work, in an attempt to minimize it. This work addresses the following topics: (I) context: transmission, symptoms, diagnosis, treatment, discharge criteria, isolation and post-pandemic consequences; (II) harm and proposals: nutritional, physiological, biomechanical and psychological.